A Unitary Transformative Decision-Making Theory: An International Consensus Approach - Luca Bertocchi; Rita Gengo; Ana Choperena; Chinma Stella Adereti; Suellen Cristina Dias Emidio; Paulo Carlos Garcia; Dorothy Jones (Advances in Nursing Science, 2026)
Nursing care decision-making is a complex process historically guided by systematic-positivist and intuitive-humanistic models. However, a unified theory grounded within the Unitary Transformative Paradigm has been lacking. This study introduces the Unitary Transformative Decision-Making (U-TIDE) theory, developed through a 6-phase exaptation heuristic inquiry. U-TIDE integrates 10 core concepts: unitary dialogic engagement, unitary appreciative knowing, voluntary mutual patterning, potential for change, communicating, meaning, transformative human experience, consciousness, human betterment, and integrality. Aligned with the Functional Health Patterns and Standardized Nursing Terminologies, U-TIDE frames decision-making as a dynamic, collaborative, and transformative process that bridges Unitary Transformative Paradigm theory with practice, enriching nursing care.